Advances in Designing and Developing Vaccines, Drugs and Therapeutic Approaches to Counter Human Papilloma Virus - Dadar, Maryam; Chakraborty, Sandip; Dhama, Kuldeep; Prasad, Minakshi; Khandia, Rekha; Hassan, Sameer; Munjal, Ashok; Tiwari, Ruchi; Karthik, Kumaragurubaran; Kumar, Deepak; Iqbal, Hafiz M. N.; Chaicumpa, Wanpen (Frontiers in Immunology, 2018)
Human papillomavirus (HPV) is a viral infection with skin-to-skin based transmission mode. HPV annually caused over 500,000 cancer cases including cervical, anogenital and oropharyngeal cancer among others. HPV vaccination has become a public-health concern, worldwide, to prevent the cases of HPV infections including precancerous lesions, cervical cancers, and genital warts especially in adolescent female and male population by launching national programs with international alliances. Currently, available prophylactic and therapeutic vaccines are expensive to be used in developing countries for vaccination programs. The recent progress in immunotherapy, biotechnology, recombinant DNA technology and molecular biology along with alternative and complementary medicinal systems have paved novel ways and valuable opportunities to design and develop effective prophylactic and therapeutic vaccines, drugs and treatment approach to counter HPV effectively. Exploration and more researches on such advances could result in the gradual reduction in the incidences of HPV cases across the world. The present review presents a current global scenario and futuristic prospects of the advanced prophylactic and therapeutic approaches against HPV along with recent patents coverage of the progress and advances in drugs, vaccines and therapeutic regimens to effectively combat HPV infections and its cancerous conditions.